ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ШӘРИЯР»ДЫҢ ЖАНРЛЫҚ ҚӘСИЙЕТЛЕРИ ҲАҚҚЫНДА БИР-ЕКИ АЎЫЗ СӨЗ - Кеңесбаева, Ш.К. (SCIENCE and SOCIETY, 2016)
The article deals with the genre peculiarities of the Karakalpak folklore epos «Shariyar», the other peoples don’t have the analogy to it. The author of the article compares different points of view on this issue in Karakalpak folklore and comes to the conclusion that this epos is neither social-realistic, nor a work with an external plot, but it is a mythologically-fairy tale work.
Keywords: the epos «Shariyar»; genre peculiarities; an epos with external plot (O.Kojurov); social-realistic epos (K.Maksetov); a fairy-tale epos (I.Sagitov); a fairy tale motive; myth motive; motive eguality; myth-fairy tale epos